Cardiac troponin‐I on diagnosis predicts early death and refractoriness in acquired thrombotic thrombocytopenic purpura. Experience of the French Thrombotic Microangiopathies Reference Center. (18th December 2014) - Benhamou, Y.; Boelle, P.‐Y.; Baudin, B.; Ederhy, S.; Gras, J.; Galicier, L.; Azoulay, E.; Provôt, F.; Maury, E.; Pène, F.; Mira, J.‐P.; Wynckel, A.; et al.
Summary Background Cardiac involvement is a major cause of mortality in patients with thrombotic thrombocytopenic purpura (TTP). However, diagnosis remains underestimated and delayed, owing to subclinical injuries. Cardiac troponin‐I measurement (cTnI) on admission could improve the early diagnosis of cardiac involvement and have prognostic value. Objectives To assess the predictive value of cTnI in patients with TTP for death or refractoriness. Patients/Methods The study involved a prospective cohort of adult TTP patients with acquired severe ADAMTS‐13 deficiency (< 10%) and included in the registry of the French Reference Center for Thrombotic Microangiopathies. Centralized cTnI measurements were performed on frozen serum on admission. Results Between January 2003 and December 2011, 133 patients with TTP (mean age, 48 ± 17 years) had available cTnI measurements on admission. Thirty‐two patients (24%) had clinical and/or electrocardiogram features. Nineteen (14.3%) had cardiac symptoms, mainly congestive heart failure and myocardial infarction. Electrocardiogram changes, mainly repolarization disorders, were present in 13 cases. An increased cTnI level (> 0.1 μg L−1) was present in 78 patients (59%), of whom 46 (59%) had no clinical cardiac involvement. The main outcomes were death (25%) and refractoriness (17%). Age (P = 0.02) and cTnI level (P = 0.002) showed the greatest impact on survival. A cTnI level of > 0.25 μg L−1 was the only independent factor in predicting death (odds ratio [OR] 2.87; 95% confidence interval [CI] 1.13–7.22; P = 0.024) and/or refractoriness (OR 3.03; 95% CI 1.27–7.3; P = 0.01). Conclusions A CTnI level of > 0.25 μg L−1 at presentation in patients with TTP appears to be an independent factor associated with a three‐fold increase in the risk of death or refractoriness. Therefore, cTnI level should be considered as a prognostic indicator in patients diagnosed with TTP.